2021
DOI: 10.1111/tbed.14216
|View full text |Cite
|
Sign up to set email alerts
|

Xenodiagnosis in four domestic cats naturally infected by Leishmania infantum

Abstract: Leishmaniasis is a neglected tropical disease that continues to pose a serious public health problem. Albeit dogs have long been held as the major reservoirs of Leishmania infantum, the involvement of domestic cats in the zoonotic cycle of visceral leishmaniasis has gained prominence. Here, 240 cats were evaluated by clinical signs and haematological/biochemical changes compatible with leishmaniasis and were diagnosed by serological, molecular, and parasitological techniques. Thus, four cats naturally infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…It was interesting to find out that almost half of the ITS1 HRM PCR-positive cats, 5 of 11, were infected with L. tropica . The detection of L. tropica infection in several cats in the study region indicates that cats are frequently exposed to this infection, can serve as sentinels for the presence of L. tropica and may also serve as reservoirs able to infect sand flies, as has been shown experimentally for L. infantum in cats in Europe and South America [ 30 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…It was interesting to find out that almost half of the ITS1 HRM PCR-positive cats, 5 of 11, were infected with L. tropica . The detection of L. tropica infection in several cats in the study region indicates that cats are frequently exposed to this infection, can serve as sentinels for the presence of L. tropica and may also serve as reservoirs able to infect sand flies, as has been shown experimentally for L. infantum in cats in Europe and South America [ 30 32 ].…”
Section: Discussionmentioning
confidence: 93%
“…Xenodiagnosis, previously used only for humans [ 88 ], is an exciting avenue to explore; it is a sensitive and specific tool to identify trypanosomes in animal and human hosts. Unfortunately, although used for Leishmania [ 89 ] and T. cruzi detection in Latin America [ 90 ], it has been limited to experimental infections for African trypanosomes [ 91 ].…”
Section: Individual Status Inferred From Current Diagnostic Toolsmentioning
confidence: 99%
“…(Psychodidae) [19,25], but L. infantum has been isolated in fleas, ticks, and other arthropods, so they could also play an important role in the transmission even in cats [40,41]. Despite the fact that vertical and horizontal transmission are not well studied in felines [42], Vioti et al (2021) have demonstrated by in vivo studies that infected cats are capable of transmitting L. infantum to sandflies [43]. Positive tests of L. infantum in cats have been reported in different countries in Europe and with different methods in the last twenty years (Table 1), showing the increasing relevance of cats in the transmission of the disease.…”
Section: Epidemiology Of Feline Leishmaniosismentioning
confidence: 99%